How (Not) to Raise Money - Goeree, Jacob K.; Maasland, Emiel; Onderstal, Sander; Turner, John L. (Journal of Political Economy, 2005)
We show that standard winner‐pay auctions are inept fund‐raising mechanisms because of the positive externality bidders forgo if they top another’s high bid. Revenues are suppressed as a result and remain finite even when bidders value a dollar donated the same as a dollar kept. This problem does not occur in lotteries and all‐pay auctions, where bidders pay irrespective of whether they win. We introduce a general class of all‐pay auctions, rank their revenues, and illustrate how they dominate lotteries and winner‐pay formats. The optimal fund‐raising mechanism is an all‐pay auction augmented with an entry fee and reserve price.